The Reverse Lunge: A Descriptive Electromyographic Study - Barbara J. Hoogenboom; Madison Ferguson; Zac Krauss; Stephanie Tran (Applied Sciences)
Limited studies exist examining the reverse lunge. The purpose of this study was to describe the activation of the rectus femoris (RF), biceps femoris (BF), gluteus medius (GMed), and gluteus maximus (GMax) of both limbs during a bodyweight reverse lunge movement. A secondary purpose was to describe the phases of the stationary (non-moving) and lead (moving) limbs during the reverse lunge. Surface electromyography (EMG) was used to record the activity of the target muscles in 20 healthy adults (10 male, 10 female; aged 22–25). Root mean squared values for mean maximum and average percent activation normalized to maximum voluntary isometric contraction (MVIC) activation were calculated. Descriptive terminology was created to describe the phases of the lunge for both limbs. The mean maximum percentage of muscle activation for the RF and BF was greater in the lead limb, while GMed and GMax activations were greater in the stationary limb. Only the lead limb RF and stationary limb GMed reached a strengthening stimulus in mean maximum percentage measurements. Clinically, it may be important to consider when each muscle is maximally active and at what percentage of its MVIC to properly prescribe the reverse lunge in a safe manner.